A quasi‐experimental evaluation of rent assistance for individuals experiencing chronic homelessness. Issue 8 (20th September 2017) - Pankratz, Courtney; Nelson, Geoffrey; Morrison, Marie
Abstract: This study investigated the effectiveness of the addition of rent assistance to existing housing and support services in the Waterloo region of Ontario for people experiencing chronic homelessness. A nonequivalent comparison group design was used to compare the outcomes between (a) participants selected to receive rent assistance plus support services (n = 26) and (b) participants receiving support services only (n = 25). Participants were interviewed at baseline and 6 months later. Participants in the rent assistance condition showed significantly greater improvements over time relative to the comparison group in housing stability and quality of life. They also demonstrated significantly better perceived housing quality, and there were trends of greater improvement in community functioning, social support, and food security. The findings demonstrate that rent assistance is associated with superior program outcomes for people experiencing chronic homelessness and is a necessary component of supported housing models, such as Housing First.